Maternal and perinatal outcome in meconium stained amniotic fluid at term: a case control study - Samiyappa, Dhana Priya; Ghose, Seetesh; John, Lopamudra B.; Samal, Rupal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Fetal well-being has traditionally been evaluated on the basis of fetal activity, FHR and presence of meconium in liquor in vertex presentation. Passage of meconium is considered physiological sign of fetal maturity on one hand and a sign of fetal distress and response to hypoxic insult on the other hand. Methods: Pregnant women of 37 - 42weeks gestation with singleton pregnancy and cephalic presentation admitted in labour ward of Mahatma Gandhi Medical College and Research Institute with clear or meconium stained amniotic fluid following spontaneous rupture or ARM were included in the study. Outcome measures were fetal heart rate abnormality, mode of delivery, Apgar score, NICU admission and diagnosis of MAS. Results: A total of 678 pregnant women were studied. Of them 226 had meconium stained and taken as study group. Rest 452 served as control group. The average gestational age of study group was 39.26±0.81. Abnormal FHR was observed in 56%.Spontaneous vaginal delivery was observed in 27.9% cases, instrumental delivery in 21.2% and caesarean section was 50.9% cases. Rate of low Apgar score 4.4% and it was two times higher in study group. NICU admission was observed in 46.7% cases of exposed group. Incidence of MAS in our study was 1.3%. Conclusions: In low resource settings where fetal scalp pH, and umbilical card lactate estimation facilities are not available, association of MSL with abnormal FHR can be taken as fetal distress and hence consideration of early operative intervention is necessary.